Differences in density and particles of the left and right in patients with type 2 diabetes mellitus and non-diabetes mellitus: A descriptive study - Hadiputri, Felicia; Epsilawati, Lusi; Damayanti, Merry Annisa; Tjahajawati, Sri; Hadikrishna, Indra (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: One of the complications of diabetes melitus is the impairment of bone health. Various analyses can be used to assess bone quality in patients with type 2 DM, including calculating the number of particles and bone density. This study aims to examine the differences in the density and particles count values of the left and right mandibular bones in patients with and without type 2 DM. Methods: This research utilized an observational descriptive method with a cross-sectional study design. The population comprised all panoramic radiographs from patients with and without T2DM, while the sample was determined by selecting data that met specific criteria. A total of 34 radiographs with T2DM and 34 radiographs without T2DM were included in the study. ImageJ software was used to analyze the density and the number of bone particles of each panoramic radiograph, both on the left and right side. The data were processed with statistical analysis, specifically the Mann-Whitney U test with significance determined at a p-value >0.05. Results: The average density values for the right and left sides in patients with T2DM were 92.998, while in patients without T2DM, it was 102.582. The difference in mandibular density was significant, with p-values 0.01 for the right side and 0.009 for the left side.The average number of bone particles in patients with T2DM is 24.087, compared to 25.205 in patients without T2DM, and not significantly different, with p-values 0.466 for the right side and 0.051 for the left side. Conclusions: Differences in mandibular density were observed between patients with and without T2DM, leading to increased fragility of the mandibular bone in T2DM patients. However, no significant differences were found in the number of bone particles between patients with and without T2DM.Perbedaan densitas dan partikel tulang mandibula kiri dan kanan pada penderita diabetes melitus tipe 2 dan bukan diabetes melitus tipe 2 menggunakan : studi deskriptifABSTRAK Pendahuluan: Salah satu komplikasi diabetes melitus adalah terganggunya kesehatan tulang. Banyak analisis yang dapat digunakan untuk menilai kualitas tulang pada penderita DM tipe 2, seperti menghitung jumlah partikel dan densitas tulang. Tujuan penelitian ini adalah melihat perbedaan nilai densitas dan jumlah partikel pada tulang mandibula kiri dan kanan pasien penderita dan bukan penderita DM tipe 2. Metode: Penelitian ini dilakukan dengan metode deskripsi observasional dengan pendekatan cross-sectional. Populasi merupakan semua radiograf panoramik dari pasien penderita dan bukan penderita DM tipe 2, sedangkan sampel ditentukan dengan memilih data yang sesuai kriteria. Data keseluruhan yang terkumpul berjumlah 34 radiograf dari pasien penderita DM tipe 2 dan 34 radiograf pada pasien bukan penderita DM tipe 2. Setiap radiograf panoramik, baik mandibula kiri maupun kanan, dianalisis nilai densitas dan jumlah partikelnya menggunakan software ImageJ. Data kemudian diolah dengan uji statistik Mann-Whitney U dengan p-value >0,05 dianggap signifikan. Hasil: Nilai rerata densitas kanan dan kiri pasien penderita DM tipe 2 adalah 92,998 dan pasien bukan penderita DM tipe 2 adalah 102,582. Perbedaan densitas bernilai signifikan dengan p-value 0,01 pada sisi kanan dan 0,009 pada sisi kiri. Nilai rata-rata partikel tulang pasien penderita DM tipe 2 adalah 24,087 dan pasien bukan penderita DM tipe 2 adalah 25,205, namun tidak berbeda signifikan, dengan p-value 0,466 untuk sisi kanan dan 0,051 untuk sisi kiri. Simpulan: Ditemukan perbedaan pada nilai densitas pasien penderita DM tipe 2 dibandingkan dengan pasien bukan penderita DM tipe 2. Hal ini menyebabkan tulang mandibula menjadi lebih rapuh sekalipun jumlah partikel tulang pada pasien penderita DM tipe 2 tidak mengalami perbedaan dibandingkan pasien bukan penderita DM tipe 2.